A new genus and species of galeommatoid bivalve (Mollusca: Bivalvia: Montacutidae) from Kuwait Bay, Arabian Gulf. Issue 2 (3rd April 2017) - Oliver, P. Graham; Skryabin, Valeriy A.; Al-Ghunaim, Aws Y.
Abstract : Larissamya comta gen. n., sp. n., is described from Kuwait Bay, northern Arabian Gulf. The hinge is identical to that seen in Kurtiella and Montacutona but the spined dorsal margin is unique. Anatomically Larissamya differs from Kurtiella in retaining both gill demibranchs and from both Kurtiella and Montacutona in having greatly unequal adductor muscles. Co-occurrence and density data suggest that L. comta may be associated with the ophuroid Amphiura fasciata . http://www.zoobank.org/urn:lsid:zoobank.org:pub:ECCB79FC-6EB2-4693-B1D4A014CB17C6D8